2021
DOI: 10.1016/j.neurobiolaging.2020.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Inherited risk of dementia and the progression of cerebral small vessel disease and inflammatory markers in cognitively healthy midlife adults: the PREVENT-Dementia study

Abstract: Cerebral small vessel disease (SVD) and inflammation are increasingly recognized as key contributors to Alzheimer's disease (AD), although the timing, trajectory, and relation between them early in the disease process is unclear. Therefore, to investigate very early-stage changes, we compared 158 healthy midlife adults with and without inherited AD predisposition (APOE4 carriership (38% positive), parental family history (FH) of dementia (54% positive)) on markers of SVD (white matter hyperintensities (WMH), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
(47 reference statements)
3
11
0
Order By: Relevance
“…This result was consistent with previous studies from the same cohort that have reported significant negative associations of CAIDE scores with visuospatial functions and navigational abilities (Ritchie et al, 2018;Ritchie et al, 2017). We did not observe a longitudinal effect, similarly to other studies of this cohort (Dounavi et al, 2021;Low et al, 2021), possibly due to the relatively young age range of the sample and the short follow-up window (Ritchie et al, 2018;Ritchie et al, 2017). We caution that the interpretability of the effect of risk on each individual function is limited by their composite assessment in this study and requires individuation in future studies with a longer longitudinal follow-up window.…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with previous studies from the same cohort that have reported significant negative associations of CAIDE scores with visuospatial functions and navigational abilities (Ritchie et al, 2018;Ritchie et al, 2017). We did not observe a longitudinal effect, similarly to other studies of this cohort (Dounavi et al, 2021;Low et al, 2021), possibly due to the relatively young age range of the sample and the short follow-up window (Ritchie et al, 2018;Ritchie et al, 2017). We caution that the interpretability of the effect of risk on each individual function is limited by their composite assessment in this study and requires individuation in future studies with a longer longitudinal follow-up window.…”
Section: Discussionsupporting
confidence: 93%
“…We found no significant associations between non-modifiable risk factors (family history of dementia, APOE4) and midlife SVD burden. This is consistent with preliminary results published by our group on a subset of PREVENT-Dementia participants [ 34 , 35 ] and represents the largest investigation of its kind in healthy middle-aged adults at present. However, contrasting results exist.…”
Section: Discussionsupporting
confidence: 93%
“…The use of composite cognitive domains that capture slightly different functions in the two assessment points [35] prevents investigation of the impact of lifestyle on cognitive changes over time in this study. Nevertheless, previous studies from this cohort have shown only subtle changes over the two-year period [75][76], possibly due to the relatively young age range of the sample and the short follow up window [34,55]. Therefore, future studies that follow this cohort over a longer period and test hypotheses informed by the previous study waves are needed to determine the longitudinal impact of lifestyle activities in cognitively healthy middle-aged individuals at risk for late life AD.…”
Section: Methodological Considerationsmentioning
confidence: 95%